2019
DOI: 10.2147/ott.s227834
|View full text |Cite
|
Sign up to set email alerts
|

<p>Aberrant Expression of miR-592 Is Associated with Prognosis and Progression of Renal Cell Carcinoma</p>

Abstract: PurposeMicroRNAs have recently reported playing a vital role in the development of cancers. However, the role of miR-592 in renal cell carcinoma (RCC) has not been explored. In this study, the potential role of miR-592 was investigated in RCC.Patients and methodsThe expression of miR-592 was evaluated in RCC tissues and cell lines using qRT-PCR assays. The Kaplan-Meier analysis and Cox proportional hazards model analysis was used to analyze the prognostic value of miR-592 in RCC. The effects of miR-592 on cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 39 publications
0
3
1
Order By: Relevance
“…These results are contrary to several other studies showing that they usually act as tumor suppressors in pancreatic, colorectal, prostate, breast, and other cancers [21][22][23][24][25][26]. Similar to our studies, the overexpression of hsa-miR-592 was also described in progression of renal cell carcinoma, colorectal carcinoma with unaffected mismatch repair mechanisms, and gastric cancer [27][28][29]. In the case of hsa-miR-1247, its upregulation, contrary to our study, has shown its tumor suppressing properties in pancreatic carcinoma as well as in neuroblastoma [30,31].…”
Section: Discussioncontrasting
confidence: 59%
“…These results are contrary to several other studies showing that they usually act as tumor suppressors in pancreatic, colorectal, prostate, breast, and other cancers [21][22][23][24][25][26]. Similar to our studies, the overexpression of hsa-miR-592 was also described in progression of renal cell carcinoma, colorectal carcinoma with unaffected mismatch repair mechanisms, and gastric cancer [27][28][29]. In the case of hsa-miR-1247, its upregulation, contrary to our study, has shown its tumor suppressing properties in pancreatic carcinoma as well as in neuroblastoma [30,31].…”
Section: Discussioncontrasting
confidence: 59%
“…When comparing the remaining potential miRNAs, according to the present bioinformatics analysis (miR-93-5p, miR-23c, miR-210-3p, miR-221-3p, and miR-592), all were suggested with important roles in PC screening [61], aggressiveness [8,62,63], and recurrence [7,18,64], or even new etiological values [65] were suggested. These miRNAs have also been highlighted with carcinogenic effects in other tumors, such as endometrial [66,67], osteosarcoma [68], hepatocellular [69], renal [17,70], or colorectal [71], among others [72][73][74]. According to our experimental analysis, miR-210-3p, miR-23c, and miR-592 were suggested as aggressiveness biomarkers in PC and miR-93-5p, miR-130b, and miR-141 were suggested as diagnostic biomarkers for this tumor.…”
Section: Discussionmentioning
confidence: 62%
“…As can be seen, there are many aspects that indicate miR-592 with interest for cancer aggressiveness biomarker and also for prognosis and therapeutics in patients with renal cell carcinoma. An over-expression of miR-592 is suggested to promote proliferation, migration, and invasion of renal cell carcinoma cells by targeting SPRY2 (gene related to PI3K/AKT and MAPK/EPK signaling pathways) [17]. In PC, there are also data relating miR-592 with aggressiveness in combination with ANPEP, miR-217, and miR-6715b [18].…”
Section: Introductionmentioning
confidence: 99%
“…Pan Z. et al have proposed that a high level of miR-592 serves as an indicator of a poorer prognosis in CRC patients [ 33 ]. However, it is worth noting that miR-592 expression has also been observed in other types of cancer, including renal cell carcinoma, prostate cancer, gastric cancer, and retinoblastoma cancer [ [35] , [36] , [37] ]. In 2017, Wang W. discussed the inhibitory effects of miR-592 on the proliferation, migration, and invasion of hepatocellular carcinoma through its targeting of IGF-1R [ 38 ].…”
Section: Discussionmentioning
confidence: 99%